Headache providers' perspectives of headache diaries in the era of increasing technology use: a qualitative study - Minen, Mia; George, Alexis; Lebowitz, Naomi; Katara, Aarti; Snyder, Ivy (Frontiers in Neurology, 2024)
Background No matter what type of headache is being considered across various populations, one of the mainstays of headache medicine is headache tracking. This self-management tool enables patients and their providers to understand patients' underlying symptoms and the effects of treatments they have tried. This is important to determining whether headaches are related to menses for women's health, to determining the time of headache occurrence, e.g., hypnic headache, and the location and duration of symptoms, e.g., trigeminal autonomic cephalgia. Prior research has investigated what people with headaches perceive about headache diary use and how people with headaches utilize electronic headache diaries. However, headache providers' perspectives on the important factors related to headache diaries are less known. Previously, using the Modified Delphi Process, a panel of four experts opined what they perceived as the most important factors for a headache diary. We sought to better understand headache providers' perspectives about headache diary/app usage from providers working in various institutions nationwide. Methods We conducted 20 semi-structured qualitative interviews of headache providers across the US from various institutions and asked them their perspectives on headache diary use. We transcribed the interviews, which two independent coders then coded. Themes and subthemes were developed using grounded theory qualitative analysis. Results Six themes emerged: (1) Providers were generally agnostic regarding the headache tracking method, but nearly all recommend the use of smartphones for tracking; (2) Providers had concerns regarding the accessibility of headache trackers; (3) Providers noted benefits to integrating headache tracking data into the EMR but had mixed opinions on how this integration might be done; (4) Providers had mixed opinions regarding the utility and interpretation of the data, specifically regarding data accuracy and efficiency; (5) Providers generally felt that headache tracking lends itself to more collaborative plan management; (6) Providers recommend behavioral health apps for patients but stated that there are few digital behavioral health interventions for headache specifically. Conclusion Interviews of headache providers, recommenders, and users of headache data are vital informants who can provide a robust amount of information about headache diary development, use in different populations, integration, and more.